The Association of Creactive Protein Levels in Second Trimester of Pregnancy with Preeclampsia - Nasruddin, Zulfaekasari; Lukas, Efendi; Malinta, Umar; Chalid, Maisuri T (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To determine C-reactive protein in second trimesterof pregnancy women who preeclamptic and non-preeclampticwomen, and to determine the relationship between the level ofC-Reactive protein of trimester two pregnancy and preeclampsiaoccurrence.Methods: This was a prospective study conducted at the policlinicsof network of academic hospitals of the Department of Obstetricsand Gynecology of Faculty of Medicine, Universitas Hasanuddin andpoliclinic of child and mother, and some Public Health Centers inMakassar city from September 2015 - April 2016. The C-reactiveprotein 115 level of pregnant women in pregnancy age of 24-28weeks was checked, whether the subjects underwent preeclampsiauntil the childbirth process. Statistics analysis used Fisher’s exacttest and Mann Whitney test.Results: The result indicate that 9 subjects (7.8%) developedpreeclampsia and 106 subjects did not become preeclampsia. Thelevel of C-Reactive protein increased in preeclampsia group comparedto non preeclampsia group i.e 5.05  1.153 : 3.36  0.265,but statistically the result is not significant (value p>0.05).Conclusion: The average score of C-Reactive protein of preeclampsiagroup is 33.5% higher than non-preeclampsia group,even though these results cannot be used as the score to predictthe preeclampsia occurrence.Keywords: C-reactive protein, preeclampsia, second trimesterpregnancy